Efectividad de los métodos no farmacológicos para la deshabituación tabáquica en atención primaria - Sanz Pozo, B. (Aten Primaria, 2003)
OBJECTIVE: To determine the effectiveness of a systematic and intensive programme of tobacco counselling, as against brief anti-tobacco counselling DESIGN: Controlled and randomised clinical trial SETTING: Primary care medical and nursing clinics at an urban Health Centre in Getafe PARTICIPANTS: Smokers who request health care at the medical clinics for any reason during the recruitment period, who satisfy the inclusion criteria and who want to take part in the study. The inclusion criteria are: 18 years old or more, people who have smoked daily during the previous month any amount of cigarettes, and high motivation (score over 7 on the Richmond test) INTERVENTION: The 110 patients recruited by each doctor will be included, depending on the clinic they come from, in the control group (brief counselling) or the intervention group (intensive counselling). For the patients in the intervention group, monitoring visits will be programmed for 6 months after giving up. Both groups will be called by phone after a year to see if they are still smoking MAIN MEASUREMENTS: Abstinence at 12 months SECONDARY MEASUREMENTS: a) Recorded at the start: personal details, medical history and smoking history; b) recorded at the consultations: abstinence, date of first giving up and symptoms of withdrawal syndrome DISCUSSION: The study will define the role ofnursing professionals in taking patients offtobacco and will help define theeffectiveness of non-medical methods toachieve this